2013
DOI: 10.1136/bmj.f2907
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' estimation of calorie content at fast food restaurants: cross sectional observational study

Abstract: Objective To investigate estimation of calorie (energy) content of meals from fast food restaurants in adults, adolescents, and school age children.Design Cross sectional study of repeated visits to fast food restaurant chains. Conclusions People eating at fast food restaurants underestimate the calorie content of meals, especially large meals. Education of consumers through calorie menu labeling and other outreach efforts might reduce the large degree of underestimation. Setting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 24 publications
(14 reference statements)
8
93
0
1
Order By: Relevance
“…This is problematic because consumers often underestimate calories and fat in foods eaten away from home. 35 Participants in this study had limited time to eat at work, so they wanted simple color-coded information that allowed them to judge at a glance whether a product had too many calories or too much saturated fat. They wanted this information next to the target meal or product, on menu boards and places where they lined up for food.…”
Section: Discussionmentioning
confidence: 99%
“…This is problematic because consumers often underestimate calories and fat in foods eaten away from home. 35 Participants in this study had limited time to eat at work, so they wanted simple color-coded information that allowed them to judge at a glance whether a product had too many calories or too much saturated fat. They wanted this information next to the target meal or product, on menu boards and places where they lined up for food.…”
Section: Discussionmentioning
confidence: 99%
“…We focus in the current work on portion-size sensitivity for unhealthy foods, recognizing that their consumption is likely more linked to obesity, and that much prior work has focused primarily on them (e.g., Block et al, 2013;Brogden & Almiron-Roig, 2011;Bryant & Dundes, 2005;Geier, Rozin, & Doros, 2006;Hernández et al, 2006;Just & Wansink, 2013). Thus, we include numerous foods that are classified as unhealthy based on their level of processing (i.e., they contained significant added fat or added sugar).…”
Section: The Current Studymentioning
confidence: 99%
“…47 People are also notoriously bad at estimating the calories in restaurant food. 48 Research on the effectiveness of menu labeling is mixed; some studies [49][50][51][52][53][54] found it promotes lowercalorie purchases or consumption, whereas others [55][56][57][58][59] have found minimal effects. Several behavioral science insights offer suggestions for ways to improve menu labeling.…”
Section: Menu Labeling: Status Quo Bias Compensation and Simplicitymentioning
confidence: 99%